2009
DOI: 10.1080/15475440802340101
|View full text |Cite
|
Sign up to set email alerts
|

Speech Segmentation in a Simulated Bilingual Environment: A Challenge for Statistical Learning?

Abstract: Studies using artificial language streams indicate that infants and adults can use statistics to correctly segment words. However, most studies have utilized only a single input language. Given the prevalence of bilingualism, how is multiple language input segmented? One particular problem may occur if learners combine input across languages: the statistics of particular units that overlap different languages may subsequently change and disrupt correct segmentation. Our study addresses this issue by employing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
157
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(176 citation statements)
references
References 44 publications
13
157
6
Order By: Relevance
“…Any information irrelevant to the initial regularities may be blocked for processing through selective attention (Broadbent, 1958;Conway, Cowan, & Bunting, 2001). This is consistent with previous studies on statistical learning that also demonstrate the blocking of subsequent new information by the exposure to the initial structure (Gebhart et al, 2009;Weiss, Gerfen, & Mitchel, 2009). Participants in Experiments 3 and 6 failed to learn the new regularities based on their performance in the test phase.…”
Section: Discussionsupporting
confidence: 89%
“…Any information irrelevant to the initial regularities may be blocked for processing through selective attention (Broadbent, 1958;Conway, Cowan, & Bunting, 2001). This is consistent with previous studies on statistical learning that also demonstrate the blocking of subsequent new information by the exposure to the initial structure (Gebhart et al, 2009;Weiss, Gerfen, & Mitchel, 2009). Participants in Experiments 3 and 6 failed to learn the new regularities based on their performance in the test phase.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, it is unclear whether the learning of stimulus bundles can be a useful perspective to understand the observed order-sensitive behavior in those experiments. Implicit learning paradigms are less affected by this concern, because the outcome of learning can only be attributed to the statistics of the input (51,52). We hope that our results here will provide a new perspective on alternative designs that tease apart the effect of learning stimulus bundles from that of reward in such tasks.…”
Section: Discussionmentioning
confidence: 84%
“…First, pairing different voices with different language input sets has been shown to help both adults (Weiss et al, 2009) and infants (Gonzales et al, 2011) to segregate the languages. Second, correlated cues generally facilitate language learning.…”
Section: Implications Of the Results For Our Understanding Of Early Wmentioning
confidence: 99%
“…First, in a different paradigm, both adults (Weiss et al, 2009) and infants (Gonzales et al, 2011) have been shown to segregate two differently structured artificial languages better when they are spoken by two different voices. Still, the task of segregating and learning artificial languages is quite different from the present word-learning task.…”
Section: Predictions When Talker Variability Is Correlated With Novelmentioning
confidence: 99%